2002
DOI: 10.1073/pnas.182425199
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of amyloid-β aggregation and caspase-3 activation by the Ginkgo biloba extract EGb761

Abstract: Standardized extract from the leaves of the Ginkgo biloba tree, labeled EGb761, has been used in clinical trials for its beneficial effects on brain functions, particularly in connection with agerelated dementias and Alzheimer's disease (AD). Substantial experimental evidence indicates that EGb761 protects against neuronal damage from a variety of insults, but its cellular and molecular mechanisms remain unknown. Using a neuroblastoma cell line stably expressing an AD-associated double mutation, we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
247
0
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(276 citation statements)
references
References 37 publications
(40 reference statements)
9
247
0
14
Order By: Relevance
“…6 As Ab is toxic to neurons, 7 the main targets for therapeutic intervention of the Ab cascade include the inhibition of Ab production, the inhibition of Ab aggregation and fibril formation, in addition to the inhibition of the consequent inflammatory responses caused by the Ab deposition. In this context, several substances are known to inhibit Ab fibrillogenesis in vitro, including laminin, 6,8 melatonin, 9 nordihydroguaiaretic acid, 10 polyphenols, 11 site-directed monoclonal antibodies, 12 a1-antichymotrypsin, 13 Ginkgo biloba extract, 14 type IV collagen 15 and b-sheet breaker peptides. 16 Nevertheless, an effective therapeutic approach that interferes directly with the neurodegenerative process in AD is eagerly awaited.…”
Section: Introductionmentioning
confidence: 99%
“…6 As Ab is toxic to neurons, 7 the main targets for therapeutic intervention of the Ab cascade include the inhibition of Ab production, the inhibition of Ab aggregation and fibril formation, in addition to the inhibition of the consequent inflammatory responses caused by the Ab deposition. In this context, several substances are known to inhibit Ab fibrillogenesis in vitro, including laminin, 6,8 melatonin, 9 nordihydroguaiaretic acid, 10 polyphenols, 11 site-directed monoclonal antibodies, 12 a1-antichymotrypsin, 13 Ginkgo biloba extract, 14 type IV collagen 15 and b-sheet breaker peptides. 16 Nevertheless, an effective therapeutic approach that interferes directly with the neurodegenerative process in AD is eagerly awaited.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects in both systems were linked to a modulation in signaling through protein kinase C and/or modulation of cell survival/cell cycle genes (4,6). Much evidence also exists to support the potential beneficial and neuromodulatory effects of flavonoid-rich ginkgo biloba extracts, such as EGb 761, in the central nervous system (7)(8)(9). Clinical trials with EGb 761, which contains kaempferol and quercetin, have indicated beneficial effects on brain function, particularly in connection with age-related dementias and Alzheimer's disease (9,10).…”
mentioning
confidence: 99%
“…EGb 761 contains flavone glycosides (quercetin, kaempferol, isorhamnetin) and terpene lactones (ginkgolides and bilobalide) and has antioxidant and free radical-scavenging activities [21]. Translational studies have also shown its potential to inhibit amyloid-aggregation and consecutive mitochondrion-initiated apoptosis, and indicated that direct neuronal damage may actually be mediated by the amyloid toxicity [22]. …”
Section: Pharmacological Treatment Of MCImentioning
confidence: 99%